The new psychology of leadership : identity, influence, and power - Haslam, S. Alexander (Psychology Press, 2011)
This work gives an overview of the new understanding of leadership that has emerged in social and organisational psychology as part of the development of self-categorisation and social identity theories. The authors advance the argument that leadership is a group process grounded in the creation and control of group identity.